ANALISIS PRODUKTIVITAS DAN PENGHEMATAN AKIBAT KLASTERISASI SEKTOR AGROINDUSTRI DI PROVINSI LAMPUNG - Affandi, M. Irfan (Indonesian Journal of Socio Economics)
The research objectives are to analyze productivity of clusteritation economies in the agroindustrial sectors. The data analysis use survey result of medium and large industrial (1998-2005) and applying indexs to determine an clusteritationâs power. Cobb-Douglas production function was used to measure the clusteritation economies.Â  The existing of the localization and urbanization in the agroindustrial sectors were significantly proved.